HORMAD2 methylation‐mediated epigenetic regulation of gene expression in thyroid cancer. Issue 10 (24th July 2018) - Lin, Qiuyu; Hou, Sen; Guan, Feng; Lin, Chenghe
Abstract: This study is aimed to investigate the methylation level of candidate genes and its impact on thyroid carcinoma (THCA) development. Infinium Human Methylation 450 BeadChip Arrays by Illumina (Illumina HM450K) was the most popular CpG microarray platform widely used in biological and medical research. The methylation level of differentially expressed genes and their corresponding CpG sites were analysed by R programme. The expression of HORMAD2 was evaluated by qRT‐PCR and Western blot, while the methylation level was examined via methylation‐specific PCR. Cell viability, metastasis, cell cycle and apoptosis were detected by MTT assay, transwell and wound healing assay and flow cytometry, respectively, after treatment with 5‐aza‐2′‐deoxycytidine (5‐Aza). Tumour formation assay was used to analyse thyroid tumour growth in nude mice in vivo. The methylation levels of all 116 differentially expressed genes were analysed. HORMAD2 was significantly hypermethylated and its mRNA expression was inhibited in THCA cells. After treatment with 5‐Aza, HORMAD2 expression was up‐regulated in THCA cells and its overexpression can suppress thyroid cancer cell viability, mobility and invasiveness remarkably. Up‐regulation of HORMAD2 in THCA cells could prolong G0/G1 phase and shorten S phase to impede cell mitosis as well as promote thyroid cancer cells apoptosis. Furthermore, tumour formation assay showed that increased HORMAD2 level impeded tumour growth in vivo. Hypermethylation of HORMAD2 could induce THCA progression, while hypomethylation of HORMAD2 retard cell growth and mobility and facilitate apoptosis through increasing its mRNA expression.